2005
DOI: 10.1007/s10549-004-8268-z
|View full text |Cite
|
Sign up to set email alerts
|

An ecological study of the association of environmental chemicals on breast cancer incidence in Texas

Abstract: Styrene was the most important environmental toxicant positively associated with invasive breast cancer incidence in Texas, likely involving women and men of all ages. Styrene may be an important breast carcinogen due to its widespread use for food storage and preparation, and its release from building materials, tobacco smoke, and industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 43 publications
3
35
0
1
Order By: Relevance
“…This result is consistent with previous findings from ecological 21) and cohort studies 22) , with particular regard to female workers in the electronics industry 13,14,23) . In particular, Sung et al showed an increased Standardized Incidence Ratio (SIR 1.38, 95% CI 1.11−1.70) among women first employed prior to 1974, which is when the Taiwan government promulgated a regulation on solvent use, and Peplonska et al found a significantly increased risk of breast cancer (OR 1.7, 95% CI 1.1−2.7) among electronic and electric equipment manufacturers.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with previous findings from ecological 21) and cohort studies 22) , with particular regard to female workers in the electronics industry 13,14,23) . In particular, Sung et al showed an increased Standardized Incidence Ratio (SIR 1.38, 95% CI 1.11−1.70) among women first employed prior to 1974, which is when the Taiwan government promulgated a regulation on solvent use, and Peplonska et al found a significantly increased risk of breast cancer (OR 1.7, 95% CI 1.1−2.7) among electronic and electric equipment manufacturers.…”
Section: Discussionsupporting
confidence: 92%
“…An ecological study of the association between exposure to environmental chemicals and incidence of breast cancer in Texas showed a higher rate of breast cancer in counties in which Cr was released in the environment from industry, in comparison with other counties. In addition, the mean elemental contents of scalp hair of breast cancer patients showed higher levels of Cr compared to controls [49].…”
Section: Discussionmentioning
confidence: 90%
“…The number of malignant mammary tumors increased in females treated with 100 mg/L formaldehyde or methyl alcohol alone. Some malignant mammary tumors were also found in treated males [Soffritti et al (2002)] Formaldehyde in the environment has been positively associated with breast cancer risk [Coyle et al (2005)]. Greater numbers of DNA-protein cross-links were found in the white cells of breast cancer patients than in matched controls [Wu et al (2002)].…”
Section: Relative Risk Data Linking Acetaldehyde/alcohol and Leukemiasmentioning
confidence: 99%